Forces of Tool-Tissue Interaction to Assess Surgical Skill Level - Sugiyama, Taku (JAMA Surg, 2017)
IMPORTANCE: The application of optimal forces between surgical instruments and tissue is fundamental to surgical performance and learning. To date, this force has not been measured clinically during the performance of microsurgery. OBJECTIVES: To establish a normative catalog of force profiles during the performance of surgery, to compare force variables among surgeons with different skill levels, and to evaluate whether such a force-based metric determines or differentiates skill level. DESIGN, SETTING, AND PARTICIPANTS: Through installation of strain gauge sensors, a force-sensing bipolar forceps was developed, and force data were obtained from predetermined surgical tasks at the Foothills Medical Centre, University of Calgary, a tertiary care center that serves Southern Alberta, Canada. Sixteen neurosurgeons (3 groups: novice, intermediate, and experienced) performed surgery on 26 neurosurgical patients with various conditions. Normative baseline force ranges were obtained using the force profiles (mean and maximum forces and force variability) from the experienced surgeons. Standardized force profiles and force errors (high force error [HFE], low force error [LFE], and force variability error [FVE]) were analyzed and compared among surgeons with different skill levels. MAIN OUTCOMES AND MEASURES: Each trial of the forceps use was termed successful or unsuccessful. The force profiles and force errors were analyzed and compared. RESULTS: This study included 26 patients (10 [38%] male and 16 [62%] female; mean [SD] age, 43 [15] years) undergoing neurosurgery by 16 surgeons (6 in the novice group, 5 in the intermediate group, and 5 in the experienced group). Unsuccessful trial–incomplete significantly correlated with LFE and FVE, and unsuccessful trial–bleeding correlated with HFE and FVE. The force strengths exerted by novice surgeons were significantly higher than those of experienced surgeons (0.74 vs 0.00; P < .001), and force variability decreased from novice (0.43) to intermediate (0.28) to experienced (0.00) surgeons; however, these differences varied among surgical tasks. The rate of HFE and FVE inversely correlated with surgeon level of experience (HFE, 0.27 for novice surgeons, 0.12 for intermediate surgeons, and 0.05 for experienced surgeons; FVE, 0.16 for novice surgeons, 0.10 for intermediate surgeons, and 0.05 for experienced surgeons). The rate of LFE significantly increased in intermediate (0.12) and novice (0.10) surgeons compared with experienced surgeons (0.04; P < .001). There was no difference in LFE between intermediate and novice surgeons. Stepwise discriminant analysis revealed that combined use of these error rates could accurately discriminate the groups (87.5%). CONCLUSIONS AND RELEVANCE: Force-sensing bipolar forceps and force analysis may help distinguish surgeon skill level, which is particularly important as surgical education shifts to a competency-based paradigm.